Urgensi Dan Signifikansi Pendekatan Multikultural Dalam Pendidikan Agama Islam - Junaidi; Suryanto (Al-Jadwa: Jurnal Studi Islam, 2022)
Islamic religious education is a subject that is developed from the basic teachings contained in the Islamic religion. Islamic religious education subjects do not only lead students to master various Islamic teachings. But the most important thing is how students can practice these teachings in everyday life. Learning Islamic religious education based on multiculturalism is one of the learning models of Islamic religious education which is linked to the diversity that exists, whether it's the diversity of religions, ethnicities, languages and so on. This is done because there are many schools with various students who are very diverse, there are different religions, ethnicities, languages, tribes, and so on. Learning Planning of Multicultural-Based Islamic Religious Education students who are non-Muslims are given the freedom to participate in class as passive participants or leave the class and be directed to the library. The Implementation of Multicultural-Based Islamic Religious Education Learning went on as usual and the non-Muslim students apparently preferred to take part in class rather than have to leave class even though there was already a policy from school that they were allowed outside the class.